2021
DOI: 10.1002/ps.6619
|View full text |Cite
|
Sign up to set email alerts
|

Key role of juvenile hormone in controlling reproductive diapause in females of the Asian lady beetle Harmonia axyridis

Abstract: BACKGROUND The Asian lady beetle Harmonia axyridis is an important predator of several agricultural pests, including aphids and whiteflies, and thus can contribute to pest management. Commercial viability as a pest control method requires that the beetle can be mass‐reared, and that workable conditions for extended shelf‐life can be guaranteed. One of the features of Harmonia's life cycle is that it enters diapause in the adult stage when the length of the photophase starts shortening in late summer. Reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 74 publications
4
40
0
Order By: Relevance
“…There is also some evidence that JH degradation has a role in regulating diapause. In C. bowringi and H. axyridis, JH degradation facilitates lipid storage and stress tolerance during diapause preparation (Guo et al, 2019;Gao et al, 2021). In addition, a previous study from our lab indicated that the transcript abundances of the genes encoding JHE and JHEH were both significantly increased in early diapause and decreased after diapause termination in female adults of C. septempunctata (Qi et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…There is also some evidence that JH degradation has a role in regulating diapause. In C. bowringi and H. axyridis, JH degradation facilitates lipid storage and stress tolerance during diapause preparation (Guo et al, 2019;Gao et al, 2021). In addition, a previous study from our lab indicated that the transcript abundances of the genes encoding JHE and JHEH were both significantly increased in early diapause and decreased after diapause termination in female adults of C. septempunctata (Qi et al, 2015).…”
Section: Introductionmentioning
confidence: 92%
“…JH in the hemolymph and the tissues is mainly degraded by three enzymes, including JH esterase (JHE), JH epoxide hydrolase (JHEH) and JH diol kinase (JHDK) (Zhang et al, 2005) (Supplementary Figure S1). In many instances of reproductive diapause, a marked downregulation of genes encoding enzymes involved in JH biosynthesis is accompanied with the upregulation of genes involved in JH metabolism, suggesting that the JH titers during diapause are collaboratively regulated by the JH biosynthesis and degradation pathways (Chen H. et al, 2021;Ma et al, 2021a;Gao et al, 2021;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Many previous studies have revealed that juvenile hormone (JH) and 20E signaling pathways participate in the regulation of diapause. [14][15][16][17][18][19][20] The reduction of JH titer triggers female reproductive diapause in Harmonia axyridis, 21 and JH regulates reproductive diapause via the methoprene-tolerant (Met) gene in male H. axyridis. 22 Similar results also have been found in female Colaphellus bowringi.…”
Section: Introductionmentioning
confidence: 99%
“…The juvenile hormone (JH) is a sesquiterpenoid compound synthesized in the corpora allata of insects [1,2]. It is essential for regulating the physiological processes of insect growth, metamorphosis, reproduction, and immunity [3][4][5][6][7][8]. JH biosynthesis is associated with the expression of most JH biosynthetic enzymes in the corpora allata [9].…”
Section: Introductionmentioning
confidence: 99%